2018
DOI: 10.1007/s10886-018-0987-4
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore-Induced Defenses in Tomato Plants Enhance the Lethality of the Entomopathogenic Bacterium, Bacillus thuringiensis var. kurstaki

Abstract: Plants can influence the effectiveness of microbial insecticides through numerous mechanisms. One of these mechanisms is the oxidation of plant phenolics by plant enzymes, such as polyphenol oxidases (PPO) and peroxidases (POD). These reactions generate a variety of products and intermediates that play important roles in resistance against herbivores. Oxidation of the catecholic phenolic compound chlorogenic acid by PPO enhances the lethality of the insect-killing bacterial pathogen, Bacillus thuringiensis var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 91 publications
2
7
0
Order By: Relevance
“…The induction of herbivory defenses in tomato increased susceptibility to B. thuringiensis in the lepidopteran Helicoverpa zea (Lepidoptera: Noctuidae), 40 in a similar fashion to what we observed for S. exigua . In the tomato‐ Helicoverpa system, the increased susceptibility to B. thuringiensis correlated with increased plant polyphenoloxidase (PPO) and peroxidase (POD) activity, which are part of the inducible defensive armoury of tomato 40 . Interestingly, in our system we reported an increased susceptibility to B. thuringiensis also in mycorrhizal plants which had not been induced by previous herbivory and thus, no major changes in these defense related enzyme activities are expected 12,59 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The induction of herbivory defenses in tomato increased susceptibility to B. thuringiensis in the lepidopteran Helicoverpa zea (Lepidoptera: Noctuidae), 40 in a similar fashion to what we observed for S. exigua . In the tomato‐ Helicoverpa system, the increased susceptibility to B. thuringiensis correlated with increased plant polyphenoloxidase (PPO) and peroxidase (POD) activity, which are part of the inducible defensive armoury of tomato 40 . Interestingly, in our system we reported an increased susceptibility to B. thuringiensis also in mycorrhizal plants which had not been induced by previous herbivory and thus, no major changes in these defense related enzyme activities are expected 12,59 .…”
Section: Discussionsupporting
confidence: 79%
“…In the tomato-Helicoverpa system, the increased susceptibility to B. thuringiensis correlated with increased plant polyphenoloxidase (PPO) and peroxidase (POD) activity, which are part of the inducible defensive armoury of tomato. 40 Interestingly, in our system we reported an increased susceptibility to B. thuringiensis also in mycorrhizal plants which had not been induced by previous herbivory and thus, no major changes in these defense related enzyme activities are expected. 12,59 Therefore, the enhanced lethality of B. thuringiensis but also of SeMNPV in larvae reared on Fm− diets may be led by other causes.…”
Section: Discussionmentioning
confidence: 45%
“…genes in the defensive mechanisms of the plant that induces enzymes like polyphenol oxidase, catalase, lipoxygenase and peroxidase. The role of polyphenol oxidase in producing resistance in the Penisetum glaucum plant against Sclerospora graminicola was also demonstrated by [33,34]. Considering the results obtained from changes of activity of the two-peroxidase and polyphenol oxidase enzymes in this experiment it can be said that nematode after reaching root and penetrating inside the root tissue, naturally hurts the root and through a lot of intercellular movement in the root tissue reaches the nutrition place.…”
Section: Electrophoresis Of Peroxidase Isozymementioning
confidence: 52%
“…Also, it has been found that polyphenol oxidase in tomato plants is expressed very much and it is accompanied with an increase of resistance to pathogens [32]. Shikano et al (2018) identified in the roots of tomato infected with nematode generating root node Meloidogyne spp. genes in the defensive mechanisms of the plant that induces enzymes like polyphenol oxidase, catalase, lipoxygenase and peroxidase.…”
Section: Electrophoresis Of Peroxidase Isozymementioning
confidence: 99%
“…Additionally, silencing the walnut PPO genes via RNA interference technology reportedly increases the chances that the resulting plants develop necrotic plaques [8]. Many other studies have confirmed the relationship between PPOs and plant defense [9,10,11,12,13,14,15,16,17]. Studies regarding the overexpression or silencing of PPO genes have clearly demonstrated the key role of PPOs in plant defense responses.…”
Section: Introductionmentioning
confidence: 99%